POSITIVE PSYCHOLOGICAL CAPITAL AND APPROACHES TO ENHANCING - Kornpuang, Narintip; Sittisomboon, Monasit; Prachanban, Pakorn; Yuh Anchunda, Henry (Journal of Education and Innovation, 2025)
This article presents the concept and theories background, characteristics, components, assessment, and approaches to enhancing Positive Psychological Capital (PsyCap), which comprises four main components: hope, self-efficacy, resilience, and optimism. The article explains PsyCap’s characteristics as being between state-like and trait-like, and discusses key measurement tools such as PCQ, CPC-12, CPC-12R, and I-PCQ. It also presents approaches to enhancing PsyCap from both international and Thai research, covering practical training, coaching and counseling, integration in education, use of technology and digital media, organizational-level promotion, and positive psychological intervention techniques. This article is valuable for human resource and organizational development in an era of rapid change and high challenges.